2014
DOI: 10.1242/jcs.164152
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of lysosomal morphology by pathogenic LRRK2 is corrected by two-pore channel 2 inhibition

Abstract: Two-pore channels (TPCs) are endolysosomal ion channels implicated in Ca2+ signalling from acidic organelles. The relevance of these ubiquitous proteins for human disease, however, is unclear. Here, we report that lysosomes are enlarged and aggregated in fibroblasts from Parkinson disease patients with the common G2019S mutation in LRRK2. Defects were corrected by molecular silencing of TPC2, pharmacological inhibition of TPC regulators [Rab7, NAADP and PtdIns(3,5)P2] and buffering local Ca2+ increases. NAADP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
186
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 159 publications
(198 citation statements)
references
References 44 publications
(57 reference statements)
12
186
0
Order By: Relevance
“…This mutation manifests with defects in the autophagy/lysosomal degradation pathway (Hockey et al, 2015; Manzoni & Lewis, 2013). We found that in LRRK2 knockout mouse cortical astrocytes the percentage of polyP‐containing lysosomes was significantly decreased (Figure 2c,d; 0.19 ± 0.01, n  = 51 for wildtype compared to 0.13 ± 0.02, n  = 54 for LRRK2 knockout cultures; p  < .001).…”
Section: Resultsmentioning
confidence: 99%
“…This mutation manifests with defects in the autophagy/lysosomal degradation pathway (Hockey et al, 2015; Manzoni & Lewis, 2013). We found that in LRRK2 knockout mouse cortical astrocytes the percentage of polyP‐containing lysosomes was significantly decreased (Figure 2c,d; 0.19 ± 0.01, n  = 51 for wildtype compared to 0.13 ± 0.02, n  = 54 for LRRK2 knockout cultures; p  < .001).…”
Section: Resultsmentioning
confidence: 99%
“…87 In fact, a recent report evidenced altered lysosome morphology in fibroblasts from patients with the common G2019S mutation in LRRK2 (also known as PKR8), which causes an autosomal dominant form of the disease. 46 Patients with this mutation present an endolysosomal system morphology markedly disrupted and characterized by clumped and swollen lysosomes, which could reflect a trafficking defect within the endolysosomal system. 46 Defects in LRRK2…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…46 Patients with this mutation present an endolysosomal system morphology markedly disrupted and characterized by clumped and swollen lysosomes, which could reflect a trafficking defect within the endolysosomal system. 46 Defects in LRRK2…”
Section: Parkinson's Diseasementioning
confidence: 99%
See 2 more Smart Citations